2011
DOI: 10.4314/sajas.v40i4.65237
|View full text |Cite
|
Sign up to set email alerts
|

Influence of supplemental aminooligosaccharides on <i>in vitro</i> disappearance of diets for dairy cattle and its effects on milk yield

Abstract: Two experiments were conducted to evaluate the influence of supplemental aminooligosaccharides (AOS) on the disappearance and fermentation of diets for lactating cows, and its effects on milk yield and quality. In the first study, diets containing 0 or 0.2% AOS (dry matter basis) were incubated for 24, 48 and 72 h with ruminal fluid to evaluate the in vitro dry matter disappearance (IVDMD) and fermentation characteristics. The addition of AOS improved IVDMD of diets, induced higher total bacterial and cellulol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
0
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
4
0
0
Order By: Relevance
“…The results obtained in this study are consistent with the results obtained by Shibata, (1985) and Biggs and Hancock, (1998). However, Sánchez et al (2010) found that the concentrations of NH 3 -N were not modified by supplemented prebiotic. On the other hand, the decrease in NH 3 -N concentration with animal fed ration supplemented with probiotics (DFM) might have been the result of increased incorporation of ammonia into microbial protein.This result supported the results obtained from microbial protein synthesis.…”
Section: Rumen Parameterssupporting
confidence: 93%
See 1 more Smart Citation
“…The results obtained in this study are consistent with the results obtained by Shibata, (1985) and Biggs and Hancock, (1998). However, Sánchez et al (2010) found that the concentrations of NH 3 -N were not modified by supplemented prebiotic. On the other hand, the decrease in NH 3 -N concentration with animal fed ration supplemented with probiotics (DFM) might have been the result of increased incorporation of ammonia into microbial protein.This result supported the results obtained from microbial protein synthesis.…”
Section: Rumen Parameterssupporting
confidence: 93%
“…While, lower values TVF's concentrations obtained from control. These results in agreement with Li et al (2007) and Sánchez et al (2010) who provided evidence that probiotics increase volatile fatty acid (VFA), microbial protein concentrations, and stabilize the rumen pH. Similar results were reported by Al-Dabeeb and Ahmed (2002), Komonna (2007) in sheep and Shahin et al (2005).…”
Section: Rumen Parameterssupporting
confidence: 90%
“…The results obtained in this study are consistent with the results obtained by Biggs and Hancock (1998) and Soliman et al (2016). However, Sánchez et al (2010) reported that the concentrations of NH3-N were not affected by supplement prebiotic. As shown in Table (4) the total volatile fatty acids (VFAs) concentration increased (P<0.05) in all treated groups as compared with control group.…”
Section: Rumen Parameterssupporting
confidence: 92%
“…Concerning the effect of sampling time on VFAs concentration, it is clear that the concentration VFAs of was lower before feeding then increases gradually until reached the peak at 6 hours post feeding. These results are agreement with Sánchez et al (2010) stated that the probiotics increase volatile fatty acid (VFA), microbial protein concentrations, and stabilize the rumen pH. El-Ashry et al (2000) found that TVFA's concentration in the rumen was low before feeding and increased with time after feeding.…”
Section: Rumen Parameterssupporting
confidence: 87%